The role of the inhabitants of Łódź in the urbanisation of its surrounding area - Makowska-Iskierka, Marzena (Turyzm/Tourism, 2015)
This article describes the urbanisation process within the recreational region surrounding Łódź. After an introduction to theoretical issues, the topic will be the ongoing changes, their stages, and effects on various planes of this urbanisation. The emphasis is put on showing the characteristics and scale of the process, its causes and social features. The paper concludes by demonstrating the dominating influence of the inhabitants of Łódź on urbanisation processes caused by their tourism and recreational activity in this area.